234k views
9 votes
Please help me its about solving system by substitution

Please help me its about solving system by substitution-example-1

1 Answer

2 votes

Answer:

(-3, 4)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtract Property of Equality

Algebra I

  • Terms/Coefficients
  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

y = -x + 1

2x + 3y = 6

Step 2: Solve for x

Substitution

  1. Substitute in y: 2x + 3(-x + 1) = 6
  2. Distribute 3: 2x - 3x + 3 = 6
  3. Combine like terms: -x + 3 = 6
  4. Isolate x terms: -x = 3
  5. Isolate x: x = -3

Step 3: Solve for y

  1. Define equation: y = -x + 1
  2. Substitute in x: y = -(-3) + 1
  3. Simplify: y = 3 + 1
  4. Add: y = 4
User MicroSumol
by
5.6k points